ナンキョク ニオケル VLF ヒス・ソーサー ノ ハッセイ リョウイキ c. ジキケンナイ ノ ハドウ リュウシ ソウゴ サヨウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 芳野, 赳夫; ヨシノ, タケオ; 福西, 浩; フクニシ, ヒロシ; 佐藤, 夏雄; サトウ, ナツオ; 尾崎, 孝之; オザキ, タカユキ; 岩瀬, 政之; イワセ, マサユキ; YOSHINO, Takeo; FUKUNISHI, Hiroshi; et al. (1980)
P(論文) 第17次南極地域観測隊は，昭和基地に人工衛星テレメトリー受信装置を設置し，1976年4月より電離層観測衛星ISIS-1号および2号の電離層トップサイトサウンターおよびVLF広帯域放射データの受信を開始した．本論分では，第17次隊，第18次隊によるISIS-1号，2号受信データを用い，極域におけるVLFヒス・ソーサーの発生領域を調べた．その結果，ヒスの発生頻度は10-14MLTの磁気緯度75°–85°付近および20–02MLTの65°–80°付近で最大になり，一方ソーサーはヒスの領域よりもやや低緯度側に位置していることが見出された．昼間側のヒスとソーサーは，その発生領域の位置からカスプ領域の低エネルギー電子フラックスと関連が深いと思われる． Satellite data acquisition facilities for ISIS-1 and 2 were built up at Syowa Station in January 1976, and the VLF wideband and topside sounder data have been received on the routine basis since April 1976. The occurrence regions of VLF hiss and saucer emissions in the southern polar region were studied statistically by using the ISIS-1 VLF data of the 110 orbits and the ISIS-2 VLF data of the 155 orbits which were received by the 17th and 18th Japanese Antarctic Research Expedition wintering parties in 1976 and 1977. It is found that the hiss emission region with the occurrence probability larger than 50% is located at 75°–85° geomagnetic latitude in 10–14 MLT in the dayside and at 65°–80° geomagnetic latitude in 20–02 MLT in the night side, while the saucer emission region with the occurrence probability larger than 30% is located at 75°–85° in 10–18 MLT in the dayside and at 60°–70° in 18-02 MLT in the night side. It is suggested that the hiss and saucer emission regions in the dayside are closely related to field-aligned currents in the cusp region. It is also found that the altitude of the saucer emission region shows a clear seasonal variation, i e., saucer emissions are observed in the altitude range of 500–4000 km with a maximum occurrence at 2500–3000 km in the austral winter season (April-September), while they are observed at the altitude higher than 3000 km in the summer season. departmental bulletin paper